ANALYSIS OF HOSPITAL STRATEGY IN AN EFFORT TO IMPROVE FAMILY SATISFACTION OF INPATIENTS AT PROF.DR. HI ALOEI SABOE HOSPITAL - Husain, Dhea rahmatullah; Muhammad, Ikram; Mohamad, Imelda (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determine the satisfaction of patient families in hospital services and analyze hospital strategies in improving the satisfaction of inpatient families at Prof. Dr. H. Aloei Saboe Regional Hospital. This research method uses a mix method approach, Data collection techniques are distributing questionnaires to patient families and conducting interviews with hospital managers or planners, and conducting interviews with patient families. The results of this study indicate that satisfaction with hospital services seen from five dimensions of service quality on average falls into the category of satisfied or good, The two dimensions with the highest assessment are Responsiveness of Service to Patient Families with a percentage of 87.91 in the satisfied category, Service Assurance to Patient Families with a percentage of 87.75 in the satisfied category.